An Essential NRP1-Mediated Role for Tagln2 in Gastric Cancer Angiogenesis - Jin, Hongwei; Zheng, Wei; Hou, Jingjing; Peng, Huifang; Zhuo, Huiqin (Frontiers in Oncology, 2021)
Knowledge about the precise biological role and underlying mechanism of Tagln2 in tumor progression is relatively limited, especially in angiogenesis focused on tumor derived endothelial cells (ECs) has rarely been reported. Here, the function, molecular mechanism and potential clinical value of Tagln2 in gastric cancer (GC) angiogenesis were investigated. GC tissue microarrays were used to assess the expression of Tagln2 in ECs. The relationships between expression and clinicopathological features were analyzed to evaluate the clinical value of Tagln2. Gain- and loss-of-function approaches were performed in ECs to investigate the functions of Tagln2 in angiogenesis. A combination of angiogenesis antibody array, RNA-Seq analyses and a series of in vitro experiments were performed to reveal the proangiogenic mechanism mediated by NRP1. Immunohistochemistry performed on an independent tissue chip (n=75) revealed significant upregulation of Tagln2 in tumor-derived ECs which were specifically immunolabeled with CD34. Additionally, high Tagln2 levels correlated significantly with the presence of lymph node as well as distant metastases. Gain- and loss-of-function approaches highlighted the function of Tagln2 in promoting EC proliferation, motility, and capillary-like tube formation and in reducing apoptosis. Tagln2 upregulation led to significantly increased mRNA and protein levels of NRP1 and subsequently activated the NRP1/VEGFR2 and downstream MAPK signaling pathways. These data indicate the importance of Tagln2 in angiogenesis, as a potential therapeutic target, and as a candidate prognostic marker in GC.